Negatively Charged Gangliosides Promote Membrane Association of Amphipathic Neurotransmitters. (1st August 2018) - Juhola, Hanna; Postila, Pekka A.; Rissanen, Sami; Lolicato, Fabio; Vattulainen, Ilpo; Róg, Tomasz
Graphical abstract: Highlights: Anionic ganglioside GM1 facilitates membrane association of amphipathic histamine. GM1 promotes membrane association of amphipathic dopamine. GM1 does not promote membrane association of cationic acetylcholine despite its charged nature. Anionic gangliosides assist amphipathic neurotransmitters to enter membrane-buried binding sites. Abstract: Lipophilic neurotransmitters (NTs) such as dopamine are chemical messengers enabling neurotransmission by adhering onto the extracellular surface of the post-synaptic membrane in a synapse, followed by binding to their receptors. Previous studies have shown that the strength of the NT–membrane association is dependent on the lipid composition of the membrane. Negatively charged lipids such as phosphatidylserine, phosphatidylglycerol, and phosphatidic acid have been indicated to promote NT–membrane binding, however these anionic lipids reside almost exclusively in the intracellular leaflet of the post-synaptic membrane instead of the extracellular leaflet facing the synaptic cleft. Meanwhile, the extracellular leaflet is relatively rich in biologically relevant anionic gangliosides such as monosialotetrahexosylganglioside (GM1), yet the role of gangliosides in NT–membrane association is not clear. Here, we explored the role of GM1 in modulating the binding of dopamine and histamine (as amphipathic/cationic NTs) as well as acetylcholine (as a hydrophilic/cationic NT) with the post-synaptic membrane surface. Atomistic molecular dynamics simulations and free energy calculations indicated that GM1 fosters membrane association of histamine and dopamine. For acetylcholine, this effect was not observed. The in silico results suggest that gangliosides form a charge-based vestibule in front of the post-synaptic membrane, attracting amphipathic NTs to the vicinity of the membrane. The results also stress the importance to understand the significance of the structural details of NTs, as exemplified by the GM1–acetylcholine interaction. In a larger context, the NT–membrane adherence, coupled to lateral diffusion in the membrane plane, is proposed to improve neurotransmission efficiency by advancing NT entry into the membrane-embedded ligand-binding sites.